Improved Nutrition Status in Patients With Advanced Heart Failure Implanted With a Left Ventricular Assist Device. (15th January 2019) - Genev, Ivo; Yost, Gardner; Gregory, Mary; Gomez, Kayéromi; Pappas, Patroklos; Tatooles, Antone; Bhat, Geetha
Abstract: Background: Left ventricular assist device (LVAD) implantation for advanced heart failure is known to improve survival, functional capacity, and quality of life. Most patients implanted with LVADs suffer from moderate to severe malnutrition and deconditioning due to their advanced disease. The Mini Nutritional Assessment (MNA) and the short form of the survey (MNA‐SF) are 2 well‐validated clinical tools, previously used to assess patient nutrition status in numerous conditions. Earlier work has demonstrated that low nutrition scores can independently predict mortality in the LVAD population. This study explored changes in MNA scores and other clinical markers following LVAD. Methods: This retrospective study included 74 patients implanted with LVADs between 2012 and 2017. MNA or MNA‐SF along with other clinical data and nutrition indices were assessed during the preoperative workup and reassessed on average 423.9 days post LVAD. Paired‐samples t ‐tests were used to evaluate any changes. Results: Despite an average body mass index of 30.8, 28.3% of patients were classified by MNA as malnourished, and 58.5% were considered at risk prior to LVAD implantation. Post LVAD implantation, MNA scores improved from an average of 19.2–23.0 ( P < 0.001), with now only 3.8% classified as malnourished and 45.3% classified as at risk. MNA‐SF and prognostic nutritional index also improved significantly. Conclusions: This study indicates that LVAD implantation is associated with a long‐term improvement in nutrition status when compared with the preoperative heart failure state.